2015
DOI: 10.1080/01694243.2015.1087253
|View full text |Cite
|
Sign up to set email alerts
|

Response of exposed human pulp to application of a hemostatic agent and a self-etch adhesive

Abstract: Objectives: The aim of this study was to investigate the human dental pulp response after use of a hemostatic agent (Ankaferd Blood Stopper [ABS]) and a self-etching adhesive system (Clearfil Protect Bond [CPB]) in direct pulp capping.Materials and methods: For the first aim, 21 non-carious human third molar teeth scheduled for extraction were selected. Class I cavities with pulp exposures were prepared. In group 1, bleeding was controlled with sterile cotton pellets and restored with calcium hydroxide (CH) + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…These findings are consistent with the results of some early studies that found that dentin adhesives interrupted the potential of pulpal cells to express their dentinogenetic activity and resulted in an inflammatory reaction, predominantly with a chronic inflammatory cell infiltration 46,47) . Despite the negative findings of some authors, after direct pulp capping with CPB in non-carious human teeth, Parthasarathy et al observed partial hard tissue deposition 13) , and we observed the formation of a complete hard tissue bridge in our previous study 9) . Similarly in uninfected dog teeth, Akhavan et al also demonstrated odontoblast layer generation and hard tissue formation in some teeth following direct pulp capping with different bonding systems including CSE 52) .…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with the results of some early studies that found that dentin adhesives interrupted the potential of pulpal cells to express their dentinogenetic activity and resulted in an inflammatory reaction, predominantly with a chronic inflammatory cell infiltration 46,47) . Despite the negative findings of some authors, after direct pulp capping with CPB in non-carious human teeth, Parthasarathy et al observed partial hard tissue deposition 13) , and we observed the formation of a complete hard tissue bridge in our previous study 9) . Similarly in uninfected dog teeth, Akhavan et al also demonstrated odontoblast layer generation and hard tissue formation in some teeth following direct pulp capping with different bonding systems including CSE 52) .…”
Section: Discussioncontrasting
confidence: 89%
“…Dentin bonding systems have been proposed as an alternative to calcium hydroxide-based materials for direct pulp capping. It is thought that dentin bonding systems effectively seal both dentin and pulp through the formation of a properly hybridized dentin-adhesive interface, allowing complete tissue healing and tertiary dentin formation through the inherent capacity of the dentin-pulp complex [9][10][11] . Several studies have partially supported this assumption 12,13) .…”
Section: Introductionmentioning
confidence: 99%
“…HEMA can inhibit the proliferation of epithelial cells and pulpal fibroblasts [ 20 ]. However, some materials containing these components have no toxic or acceptable effects on dental pulp in vivo [ 24 , 25 ]. Traditional in vitro cytotoxicity testing combined with a monolayer cell culture cannot simulate the three-dimensional (3D) cell growth observed in vivo, which may explain the discrepancy between in vivo and in vitro study results.…”
Section: Introductionmentioning
confidence: 99%